2001
DOI: 10.1007/s003830000470
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral anterior pubic osteotomy in bladder exstrophy repair: report of increasing success

Abstract: Bilateral posterior iliac osteotomy is performed in most patients undergoing primary closure of an exstrophic bladder; the aims are to facilitate abdominal-wall closure, prevent postoperative wound dehiscene, and possibly, to achieve better urinary control in older age. A new technique, anterior pelvic osteotomy of the superior pubic ramus, seems to obtain tension-free symphysis approximation safely and quickly. We report our initial experience with this osteotomy. Five neonates, four males and one female from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
2
8
1
2
Order By: Relevance
“…This result is comparable to what is reported by Elsayed et al [16] . It is slightly lower than what is reported 100% by Chiari et al [5] , which may be due to the small sample size in the later study [table 2and graph 2]. Graph 2: Comparison of present study (no., sex, success rate) to other studies The operative time for both osteotomies ranged from 30 to 45 minutes.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…This result is comparable to what is reported by Elsayed et al [16] . It is slightly lower than what is reported 100% by Chiari et al [5] , which may be due to the small sample size in the later study [table 2and graph 2]. Graph 2: Comparison of present study (no., sex, success rate) to other studies The operative time for both osteotomies ranged from 30 to 45 minutes.…”
Section: Discussioncontrasting
confidence: 68%
“…As comparison to Chiari and Elsayed studies who reported a male incidence of 80% and 86.6% respectively [5], [16] , in present study 85.7% of the patients were males. Successful repair using bilateral anterior pelvic osteotomy of superior pubic rami in this study was achieved in 92.8% of the patients operated on.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations